The impact of encroachment of mangroves into saltmarshes on saltwater mosquito habitats. Issue 2 (December 2013) - Dale, Pat; Eslami‐Andargoli, Leila; Knight, Jon
ABSTRACT Will mangrove encroachment into saltmarshes affect saltwater mosquito habitats? To address this, we synthesized information from two perspectives: 1) at a detailed level, the immature mosquito habitat within mangroves; 2) at a more general or regional level, changes due to mangrove expansion into saltmarshes. This is a synthesis of two research projects. One showed that mosquito larval habitats in mangroves are complex, related to the detailed interactions between topography and tidal patterns and that not all parts of a mangrove forest are suitable habitat. The other, based on remote sensing and analysis of rainfall data, showed that mangrove encroachment in eastern Australia is related to both climate and human land use over several decades (1972–2004). An important question emerged: when mangroves encroach into saltmarshes will they displace saltmarsh immature mosquito habitats or will they replace them with mangrove ones? There is no simple answer: it will vary with climate change and sea level scenario and how these affect the system. We conclude that mosquito management, which is locally implemented, needs to be integrated with land use planning systems, which often operate at a more general level.